Tropical Sea Snail Shells: Possible Exotic Sources for Ceramic Biomaterial Synthesis - OKTAR, FAİK NÜZHET (AMER INST PHYSICS, 2013)
In this study, chemical and structural properties of sea snail shell based bioceramic materials (i.e. hydroxyapatite, whitlockite and other phases) are produced by using mechano-chemical (ultrasonic) conversion method. For this purpose, differential thermal and gravimetric analysis (DTA/TG), X-ray diffraction, infra-red (IR) and scanning electron microscope (SEM) studies are performed.
Keywords: Sea snail shells; mechano-chemical (ultrasonic) conversion; biomaterials; hydroxyapatite; POWDERS